Recent advances in RASopathies - Aoki, Yoko; Niihori, Tetsuya; Inoue, Shin-ichi; Matsubara, Yoichi (Journal of human genetics, 2016)
RASopathies or RAS/mitogen-activated protein kinase (MAPK) syndromes are a group of phenotypically overlapping syndromes caused by germline mutations that encode components of the RAS/MAPK signaling pathway. These disorders include neurofibromatosis type I, Legius syndrome, Noonan syndrome, Noonan syndrome with multiple lentigines (formerly called LEOPARD syndrome), Costello syndrome, cardiofaciocutaneous (CFC) syndrome, Noonan-like syndrome, hereditary gingival fibromatosis and capillary malformation-arteriovenous malformation. Recently, novel gene variants, including RIT1, RRAS, RASA2, A2ML1, SOS2 and LZTR1, have been shown to be associated with RASopathies, further expanding the disease entity. Although further analysis will be needed, these findings will help to better elucidate an understanding of the pathogenesis of these disorders and will aid in the development of potential therapeutic approaches. In this review, we summarize the novel genes that have been reported to be associated with RASopathies and highlight the cardiovascular abnormalities that may arise in affected individuals.